Analysis of Competitiveness and Impact of Government Policies on Honeybee Cultivation Business using the Policy Analysis Matrix Approach (Case Study of the Madu Mas Forest Farmer Group in South Konawe Regency) - Yunus, Lukman; Zani, Munirwan; Sarinah, Sarinah; Dedu, La Ode Arfan (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
This study aims to analyze the competitiveness and impact of government policies on honey bee farming using the Policy Analysis Matrix approach. The research was carried out at the Madu Mas Forest Farmers Group (KTH) in South Konawe Regency in April 2022. The study population was all members of the Madu Mas KTH in South Konawe Regency, totaling 15 people, all of whom were used as research samples using the census method. The research variables include tradable and non-tradable input costs, private and social prices, production, and revenues. Analysis of research data using the Policy Analysis Matrix (PAM) approach. The results showed that the honey bee farming business at KTH Madu Mas in South Konawe Regency had competitiveness based on indicators of competitive advantage as measured by the PCR value, which was 0.72. However, it does not have competitiveness based on comparative advantage indicators as measured by the DRCR value, which is equal to 2.46. Meanwhile, the impact of government policies on the output of beekeeping businesses at KTH Madu Masa in Konawe Selatan Regency causes the output value at private prices to be greater than the output value at social prices. Then, the impact of government policies on the inputs of the honey bee cultivation business at KTH Madu Mas in Konawe Selatan Regency causes the profits received to be smaller than without the policy. Keywords: competitiveness, policy impact, honey bees, PAM